Valuing a new good - Laura Blow; Ian A. Crawford (Institute for Fiscal Studies (IFS), 2004)
This paper presents a nonparametric method for calculating a lower bound on the virtual or reservation price of a new good. This allows the welfare effects of product market innovations to be investigated. We illustrate the technique using consumer panel data.
Keywords: C43; D11; 330; New goods; Revealed Preference; Innovation; Offenbarte Präferenzen; Wohlfahrtsanalyse; Nichtparametrisches Verfahren